Digital Literacy Skills Among Certified Librarians in Nigerian Libraries: Library Overview - Atanda Saliu Sambo; Abdulakeem Akoworada Imran; Mohammed Lawal Akanbi Akanbi (MO.RI Publishing, 2022)
Certified librarians in Nigeria libraries must be proactive and come on board to adopt a new intellectualizes digital literacy as a required ability that an individual must compulsorily possess. Three objectives such as types digital literacy skills, how it acquires and challenges faced by certified librarians. The study employed a social survey technique of research with a questionnaire as the research instrument. The study was carried out using the Statistical Package for the Social Sciences (SPSS) application software. The findings of this study show that the majority of certified librarians have digital literacy skills that they sponsor themselves for digital literacy training, and that some acquired digital literacy skills through trial and error among others. Certified librarians in Nigerian libraries to redouble their efforts in ensuring that these future librarians and scholars are well-trained to be digitally up-to-date in order to save the profession's future and contribute as much as possible to Nigeria's digital technology revival.